The Fingerprint of Fortified Wines—From the Sui Generis Production Processes to the Distinctive Aroma - Rosa Perestrelo; Yassine Jaouhari; Teresa Abreu; Mariangie M. Castillo; Fabiano Travaglia; Jorge A. M. Pereira; José S. Câmara; Matteo Bordiga (Foods, 2023)
The fortified wines that originated in Mediterranean countries have, in common, a high alcohol content to increase their shelf-life during long journeys to northern Europe and the American continent. Nowadays, the world’s better-known wines, including Marsala, Madeira, Port, and Sherry, due to their high alcoholic content, sweet taste, and intense aromatic profile, are designated as dessert wines and sometimes served as aperitifs. This review gives an overview of the traditional vinification process, including the microbiota and autochthonous yeast, as well as the regulatory aspects of the main Italian, Portuguese, and Spanish fortified wines. The winemaking process is essential to defining the volatile organic compounds (VOCs) that characterize the aroma of each fortified wine, giving them an organoleptic fingerprint and “terroir” characteristics. The various volatile and odorous compounds found in fortified wines during the oxidative aging are discussed in the last part of this review.